Effectiveness of Nussa and Rarra Animation in Fostering Character Education among Elementary Students in North Sangatta - Farhin, Nurul (Sahabat Akademia Group, 2025)
Character education is a crucial foundation that must be developed from an early age, especially during elementary school. In addition to parental guidance, educational media such as the Nussa and Rarra animated films can serve as an engaging and effective tool to instil moral values in children. This study aims to analyse the effectiveness of the Nussa and Rarra films in fostering character education among elementary school students in North Sangatta Village, and describe the outcomes of such character education efforts. This research uses a qualitative approach with elementary students, parents, and community members in North Sangatta Village as participants. Informants were selected using purposive sampling based on specific criteria. Data were collected through observation, interviews, and documentation, and analysed using interactive analysis techniques. The findings reveal that the Nussa and Rarra animations effectively instill character values by presenting relatable and exemplary behaviour in daily life. Children demonstrated improvements in both cognitive (knowledge) and affective (attitude) domains, and parents reported using the films as modern alternatives to teach ethical values. The study concludes that animated media can be an effective, accessible, and engaging means of character education for young learners. This research contributes to the development of media-based moral education strategies that can be integrated into both formal and informal learning settings.